Analisis Implementasi Kebijakan Project Based Learning di SMKN 1 Pacet Cianjur - Astuti, Widya Puji; Sukirman, Dadang; Rusman, Rusman (Universitas Muria Kudus, 2025)
The implementation of Project Based Learning (PjBL) in vocational schools is one of the efforts to align vocational education with the needs of the industrial world. This study aims to analyze the implementation of the Project Based Learning (PjBL) policy at SMKN 1 Pacet Cianjur and evaluate the obstacles faced and opportunities for improvement that can be applied. This study uses a qualitative approach and case study method, this study was conducted at SMKN 1 Pacet Cianjur from September to October 2024. The research data includes primary data obtained through participatory observation and secondary data from documents related to the PjBL policy in the Merdeka curriculum. Data collection techniques are carried out through observation and documentation, with instruments in the form of observation guidelines and official reference documents from the government. Validity testing is carried out by confirming the results with participants, while reliability testing is carried out by maintaining the consistency of data collection techniques. The data were analyzed using classification techniques in policy analysis studies, which in this study were categorized into four aspects, namely teacher quality, facilities and infrastructure, access to teaching materials, and learning media. The results of the study indicate that limitations in teacher competence, practice facilities, teaching materials, and digital media hinder the optimal implementation of PjBL. Recommendations for improvement include improving teacher training, providing adequate facilities, and access to relevant digital teaching materials to support the success of PjBL in vocational schools.